2022
DOI: 10.1002/gj.4625
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Carboniferous oceanic island basalts with Permian supra‐subduction zone ophiolites in the Changning–Menglian accretionary wedge: Implication for tectonic reconstruction

Abstract: This paper reports two types of basalt that have different ages (Carboniferous and Permian) but occur next to each other in the northern part of the Changning–Menglian accretionary wedge, southwestern China. We use the geochronology and geochemical data to evaluate the tectonic evolution of the Palaeo‐Tethys during this period. Zircon grains from the mafic‐ultramafic rocks associated with the Permian basalts in the Xiaomengtai area yield a U–Pb age of 281 Ma and εHf(t) values from +9.2 to +12.8. The Permian ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 116 publications
(265 reference statements)
0
1
0
Order By: Relevance
“…Ophiolites in accretionary wedges above the Palaeo‐Tethyan subduction zones are rarely preserved, with a few cases in the Longmu Co–Shuanghu, Changning–Menglian and Chiang Mai–Inthanon accretionary wedges. Liu, Deng, et al (2023) reported two types of basalt in the northern part of the Changning–Menglian accretionary wedge, representing the Carboniferous and Permian oceanic crust. The Carboniferous basalts show similar features to typical oceanic island basalts (OIBs), whereas the Permian basalts have consistent geochemical features with supra‐subduction zone (SSZ)‐type ophiolite.…”
Section: Salient Results From the Thematic Issuementioning
confidence: 99%
“…Ophiolites in accretionary wedges above the Palaeo‐Tethyan subduction zones are rarely preserved, with a few cases in the Longmu Co–Shuanghu, Changning–Menglian and Chiang Mai–Inthanon accretionary wedges. Liu, Deng, et al (2023) reported two types of basalt in the northern part of the Changning–Menglian accretionary wedge, representing the Carboniferous and Permian oceanic crust. The Carboniferous basalts show similar features to typical oceanic island basalts (OIBs), whereas the Permian basalts have consistent geochemical features with supra‐subduction zone (SSZ)‐type ophiolite.…”
Section: Salient Results From the Thematic Issuementioning
confidence: 99%